2011
DOI: 10.1136/bjo.2010.199216
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and complement factor H in aged human eyes and eyes with age-related macular degeneration

Abstract: Background There is increasing evidence that inflammation and immune-mediated processes (complement activation) play an important role in age-related macular degeneration (AMD) pathogenesis. A genetic variation in the complement factor H (CFH) gene and plasma levels of C-reactive protein (CRP), a systemic marker of subclinical inflammation, have been consistently shown to be associated with an increased risk for AMD. In the present study, we examined the immunolocalization of CRP and CFH in aged control human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 31 publications
8
98
4
Order By: Relevance
“…In the current study, the aqueous humor CRP level was significantly higher in eyes with neovascular AMD or PCV compared with control eyes. In an immunohistochemical study, Bhutto et al [17] reported that CRP is significantly higher than in controls in Bruch's membrane, choriocapillaris and choroidal stroma in human donor eyes with early or advanced AMD. In the current study, higher levels of CRP in the aqueous humor in eyes with neovascular AMD and PCV might reflect inflammation in the choroid in these eyes.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the aqueous humor CRP level was significantly higher in eyes with neovascular AMD or PCV compared with control eyes. In an immunohistochemical study, Bhutto et al [17] reported that CRP is significantly higher than in controls in Bruch's membrane, choriocapillaris and choroidal stroma in human donor eyes with early or advanced AMD. In the current study, higher levels of CRP in the aqueous humor in eyes with neovascular AMD and PCV might reflect inflammation in the choroid in these eyes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, changes in relative levels of CFH and CRP may also contribute to uncontrolled complement activation that may result in cell and tissue damage. 31 The complement system is a key component in the pathogenesis of ARMD and therefore it may play a major role in developing new therapeutic interventions. 32 The combination of antioxidants and zinc studied by the Age-Related Eye Disease Study (AREDS) was reported to reduce disease progression and visual loss in certain patients with non-exudative AMD.…”
Section: Pharmacogenomics In Age-related Macular Degeneration (Armd)mentioning
confidence: 99%
“…157 One study found people with rheumatoid arthritis had less prevalence of AMD and suggested anti-inflammatory agents, commonly used to manage the symptoms of rheumatoid arthritis, provide a protective effect against development of ARMD, 243 since there is some evidence that inflammation may play a role in the development of ARMD. 244 However, environmental and genetic factors may also be relevant as rheumatoid arthritis is commonly a disease of the young and ARMD is more apparent over 50 years of age. 245 …”
Section: Arthritismentioning
confidence: 99%